The Combination of Plant Growth Promoting Rhizobacteria (PGPR) Paitan Root with Several Types of Bokashi and Its Effect on Tatsoi - Meyuliana, Aulia; Yora, Muharama; Elinda, Friza; Miranda, Cut Nyak Dara; Sihotang, Saipul (Universitas Medan Area, 2024)
The combination of PGPR (Plant Growth Promoting Rhizobacteria) with bokashi aims to increase nutrient availability in the soil. PGPR which comes from paitan roots is known to have the potential to help nutrient availability so by combining it with bokashi it is hoped that it will optimize its potential in increasing tatsoi production. The bokashi used in this research were chicken manure bokashi and goat manure bokashi. Research design with two factors, namely five doses of PGPR and two types of bokashi. The PGPR doses used were 0 ml/L (D0), 50 ml/L (D1), 100 ml/L (D2), 150 ml/L (D3), 200 ml/L (D4) and two types of Chicken bokashi (A) and Goat Bokashi (K) with 5 repetitions. The observations measured were plant height (cm), number of leaves (strands) and crop diameter (cm). The results of the research showed that the combination of PGPR with bokashi chicken manure and bokashi goat manure did not have a significant effect on plant growth, namely plant height, number of leaves and crop diameter of tatsoi.